Pan-astronomical hermeneutics and the arts of the lamentation priest - Wee, John Z. (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2017)
The “Esoteric Babylonian Commentary” (abbr. EBC) represents an excerpt from a larger commentary tablet LBAT 1601, which was unusual in its wide scope encompassing teratology, medical diagnosis, physiognomy, cuneiform sign exercises, and magical incantations and rituals, and which reinterpreted these diverse fields of knowledge in terms of astronomical phenomena. The topics selectively excerpted into EBC by a lamentation priest suggest a compartmentalization of textual expertise, consistent with professional purviews in the late 1st millennium BCE.